PENGARUH PENGGUNAAN INFLUENCER MARKETING TERHADAP PERILAKU PEMBELIAN KONSUMEN DALAM ERA DIGITAL - Saifuddin Zuhri; Ahmad Fathur Rozi; Anjar Sulistyowati; Nurul Fauziyah (PT. Jurnal Center Indonesia Publisher, 2025)
This research aims to analyze the influence of the use of influencer marketing on consumer purchasing behavior in the digital era. Influencer marketing has become a popular marketing strategy, especially on social media, that can influence consumer purchasing decisions. This research uses a survey method with 200 respondents who actively use social media and are exposed to influencer marketing content. The variables analyzed include influencer credibility, audience engagement, product suitability to the audience, and their influence on consumer purchasing decisions. The research results show that influencer credibility, audience engagement, and product suitability with the audience have a significant positive influence on consumer purchasing behavior. Additionally, transparency and authenticity in the relationship between influencers and brands has also proven important in building audience trust. This research provides practical implications for companies to select the right influencers, increase audience engagement, and maintain authenticity in their marketing campaigns. Overall, influencer marketing has proven effective in influencing consumer purchasing decisions, especially in the context of social media and the digital era.